1998
DOI: 10.1055/s-2007-1001345
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine Injection for Sclerotherapy of Angiodysplasia of the Colon

Abstract: Our method was shown to be feasible and safe. The success of the intralesional injection of the sclerosing agent may be predicted when changes in the mucosal surface are observed: (a) immediately after the injection sufficient sclerosant is deemed to have been injected and to the proper depth in the bowel wall, if the mucosa bulges while the solution is being injected; and (b) if a shallow ulceration is seen in an early subsequent reexamination where the treated lesion was located, allowing scar tissue produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Another study demonstrated the feasibility and safety of ethanolamine injection to treat eight patients with 15 lesions predominantly in the right colon. 162 None of the studies reported any serious com-plications. However, this technique can be challenging and time consuming depending of the site, number and ease of access to the lesions.…”
Section: Endoscopic Therapiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study demonstrated the feasibility and safety of ethanolamine injection to treat eight patients with 15 lesions predominantly in the right colon. 162 None of the studies reported any serious com-plications. However, this technique can be challenging and time consuming depending of the site, number and ease of access to the lesions.…”
Section: Endoscopic Therapiesmentioning
confidence: 93%
“…used 0.5–1.0 mL of 1.5% sodium tetracedyl sulphate to treat 10 patients with upper GI AD directly injecting the sclerosant beneath the lesion. Another study demonstrated the feasibility and safety of ethanolamine injection to treat eight patients with 15 lesions predominantly in the right colon . None of the studies reported any serious complications.…”
Section: Managementmentioning
confidence: 99%
“…To prevent brisk bleeding from angiodysplasia when contact electrocautery is performed, large angiodysplasia should be cauterized from the outer margin towards the centre to obliterate feeder vessels. Injection therapy with sclerosing agents, such as ethanolamine, has also been described for control of bleeding from colonic angiodysplasia but is not widely employed 89 . Argon plasma coagulation, a noncontact method, has been used increasingly for the treatment of bleeding colonic angiodysplasia (grade B evidence) 90–92 .…”
Section: Management Approach To Patients With Acute Lower Gastrointesmentioning
confidence: 99%
“…In the past, most cases of vascular ectasia were treated endoscopically, although some cases were treated surgically 5 . Although sclerotherapy, ethanol injection, high‐frequency coagulation, thermocoagulation using a heat probe, and photocoagulation using a laser have been reported to be useful for treating vascular ectasia, a consensus of opinions has not yet been obtained 6–8 …”
Section: Discussionmentioning
confidence: 99%